Konjungsi Koordinatif dan Konjungsi Subordinatif dalam Teks Berita Kompas Terbitan September 2025 - Nur Gimas Tiaroh; Lutfi Anifatun Wahidah; Yuwen Nurkhalifah; Atikah Nuha Hibatullah; Isnaini Muyassaroh; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Zulfa Fahmy (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
Coordinating conjunctions are conjunctions that function to connect two language units that have the same or equal status, while subordinating conjunctions are conjunctions that connect two language units that do not have the same or equal status. News text is a text that contains information about factual and actual events that are still hotly discussed by the public. This study aims to analyze the use of coordinating and subordinating conjunctions in news articles published by Kompas in September 2025. The method used in this research is a descriptive qualitative method, with observation and note taking techniques applied to analyze conjunctions based on their types and functions. The results show that coordinating conjunctions such as (and, or, but, however) and subordinating conjunctions such as (because, so that, after, until, if) are used to construct coherent, logical, and easily understood sentences. The appropriate use of conjunctions supports the effective delivery of information and enhances the reader's comprehension of the news content. This research is expected to serve as a reference for readers or future researchers who wish to examine linguistic phenomena in online news texts using a similar approach.